Analisa Pengaruh Kapasitas Udara Untuk Campuran Bahan Bakar Terhadap Prestasi Mesin Diesel - Marlon Hetharia (Industrial Engineering Study Program, Pattimura University, 2012)
This research studies atmosphere capacities influence in combustion chamber ( selinder) as diesel fuel fuel mixture to Diesel engine performance. To know atmosphere capacities entering into combustion chamber is applied by measuring instrument orifice is having diameter 75,10, 125, 15,20 mm at revolution 1296 rpm constant. Atmosphere outside combustion chamber admission through orifice attached at relocation box wall of atmosphere, then this atmosphere packed into combustion chamber through induction valve by piston impulse with constant speed. From result of assaying indicates that Ever greater of atmosphere capacities, increasingly boosts up Volumetric efficiency but not forever boosts up Efisiensi thermal, Because at certain atmosphere capacities of its(the thermal efficiency declines. By using orifice is having diameter 10 mm to boost up engine performance , atmosphere capacities, Volumetric efficiency and boosts up Efisiensi thermal.